Phosphorus binding with ferric citrate is associated with fewer hospitalizations and reduced hospitalization costs. (June 2015) - Rodby, Roger; Umanath, Kausik; Niecestro, Robert; Jackson, James H; Sika, Mohammed; Lewis, Julia B; Dwyer, Jamie P
<x xml:space="preserve">Abstract</x> Background: Ferric citrate (FC) is a new phosphorus binder shown to increase serum iron stores while reducing intravenous iron and erythropoiesis-stimulating agent usage. Such reductions could lower hospitalization rates and associated costs. Methods: Hospitalizations during a Phase III trial were compared between FC and active control (AC). Hospitalization costs were estimated using the 2013 US Renal Data System Annual Data Report. Results: 34.6% of FC patients were hospitalized at least once versus 45.6% of the AC group (risk reduction 24.2%; p = 0.02). There were 181 unique hospitalizations in the FC group versus 239 in the AC group, for a difference of 58 hospitalizations. Total potential savings was US 867, 622 in hospitalization costs in the FC group. If the hospitalization reduction in our study was applied to the general end-stage renal disease population, this could translate into a savings of US 3002/patient/year. Conclusions: Patients receiving FC experienced fewer hospitalizations with the potential for significant savings.